Museu e informação: uma proposta de avaliação da ficha de catalogação do Museu do Instituto Histórico e Geográfico do Pará - REIS, Mateus da Silva (2019)
Museological documentation can be understood as one of the areas responsible for the formation and propagation of museum knowledge. This can be defined by its function in registering, organizing and disseminating the information pertaining to the museum objects that compose a collection. In this way, a documentation system for a museum is made up of instruments that enable the cataloging of these objects, instruments that are understood as inventories, listing sheet and, mainly, cataloging sheet. The cataloging sheet of a museological institution is used to record and group the maximum information of an artifact, in this way, it is understood that this instrument is one of the key pieces for the accomplishment of documentation procedures in collections. In view of this, consideration is given to the importance of evaluating a catalytic data sheet so that it functions in full efficiency. Thus, this study formulated a method that could evaluate the cataloging form of the Museum of the Historical and Geographic Institute of Pará (MIHGP), used only in the institution's gallery, making possible the investigation regarding the efficiency of the registration fields present in the file in the process of cataloging and organizing the information of the collections of the Museum. Thus, this research undertakes to perform the evaluation of this cataloging instrument, from different points of view, from the application of a questionnaire with five questions related to this instrument, where it was possible to obtain opinions about the effectiveness of the data sheet the MIHGP. It should be noted that this research is justified by the importance of analyzing a cataloging record, based on the problem of MIHGP, it does not contain any method of evaluating its documentation instruments. Finally, it was possible to obtain as a result more evident a lack of organization of the fields, as well as a non-concise nomenclature of these.